Pengaruh Pemahaman Peraturan Pajak, Tarif Pajak Dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak Restoran: (Studi Kasus Pada Restoran Di Kota Medan) - Venni Yolanda; Tri Inda Fadhila Rahma; Arnida Wahyuni Lubis (STIKes Ibnu Sina Ajibarang, 2023)
This research is based on the influence of understanding tax regulations, tax rates, and taxpayer awareness on restaurant taxpayer compliance in Medan City. This research aims to determine the effect of understanding tax regulations, tax rates and taxpayer awareness on restaurant taxpayer compliance. Understanding tax regulations is knowledge and understanding of the rights and obligations as a taxpayer, tax rates are knowledge and understanding of PKP and tax rates, taxpayer awareness is awareness that paying taxes is an obligation. and taxpayer compliance is complying with the rules set by taxation. This research uses a quantitative method with an associative approach, data collection techniques using questionnaires. The sample size in this research was 40 restaurants in Medan City. The sampling technique uses random sampling technique. Data were analyzed using multiple linear regression methods. The results of the research show that Law Number 28 of 2007 explains the General Provisions and Procedures for Taxation and Medan City Regional Regulation Number 12 of 2003 discusses restaurant taxes and the tax rates imposed, tcount for variable X1 (0.699) is smaller than ttable ( 2,028) then it can be said that partial understanding of tax regulations does not have a significant effect on restaurant taxpayer compliance and the restaurant tax rate is 10% (ten percent) of the restaurant tax base, namely the amount of payments made to restaurants, t calculated for variable X2 (2,349 ) is greater than ttable (2.028), so it can be said that the tax rate has a significant influence on restaurant taxpayer compliance, while taxpayer awareness in paying taxes is the taxpayer's behavior in the form of views or feelings involving knowledge, belief and reasoning accompanied by a tendency to acting in accordance with the regulations provided by the tax provisions system, tcount for variable The research results from the simultaneous test hypothesis with a significance level of 5% show that Fcount (9.292) is greater than Ftable (2.87) so that all independent variables consisting of understanding of tax regulations, tax rates and awareness of taxpayers simultaneously have a significant effect on the dependent variable, namely restaurant taxpayer compliance.